2014 IEEE/ASME 10th International Conference on Mechatronic and Embedded Systems and Applications (MESA) 2014
DOI: 10.1109/mesa.2014.6935597
|View full text |Cite
|
Sign up to set email alerts
|

Hammer: An Android based application for end-user industrial robot programming

Abstract: Abstract-This paper presents a novel tablet based end-user interface for industrial robot programming (called Hammer). This application makes easier to program tasks for industrial robots like polishing, milling or grinding. It is based on the Scratch programming language, but specifically design and created for Android OS. It is a visual programming concept that allows non-skilled programmer operators to create programs. The application also allows to monitor the tasks while it is being executed by overlappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 9 publications
(10 reference statements)
1
30
0
Order By: Relevance
“…Abbas et al [7] proposed the usage of mobile devices in combination with AR for industrial robot online programming. Mateo et al [8] state that the use of Android tablets in industrial robot working environments is growing and provides new means for small batch industrial applications that need fast and easy to use tools to program the robots. Tang et al [9] conducted a user study regarding the relative effectiveness of AR instructions in an assembly task.…”
Section: Introductionmentioning
confidence: 99%
“…Abbas et al [7] proposed the usage of mobile devices in combination with AR for industrial robot online programming. Mateo et al [8] state that the use of Android tablets in industrial robot working environments is growing and provides new means for small batch industrial applications that need fast and easy to use tools to program the robots. Tang et al [9] conducted a user study regarding the relative effectiveness of AR instructions in an assembly task.…”
Section: Introductionmentioning
confidence: 99%
“…On the AR side of things, projector based AR has seen use for visualizing robot's intentions and intuitive programming of robots in robot work cells [37], displaying intentions of mobile robots operating in human environments [38], as well as for debugging and rapid prototyping of robotic systems through visualization of sensor data [39]. Tablets have seen use in AR-assisted robot programming [40] as well. Devices like the Google Tango tablet, in addition, with inbuilt SLAM [41] can be used for markerless AR applications.…”
Section: Related Workmentioning
confidence: 99%
“…These developments have led to a growing interest in making it easy for domain experts to transfer knowledge to collaborative robots, either through a user interface [2], [3], [4], [5], natural language [6], or learning from demonstration [7], [8], [9], [10]. To take full advantage of these systems, the human user must have an accurate mental model of a robot's capabilities [11].…”
Section: Introductionmentioning
confidence: 99%
“…We previously proposed the CoSTAR system as a potential solution. 3 CoSTAR offers a set of planning and perceptual capabilities, united through a Behavior Tree-based task plan editor, that is designed to enable expert users to author complex plans for collaborative robots. We also demonstrated that CoSTAR allows users to solve a wide variety of problems such as sanding, assembly, and wire bending [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation